The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1021/tx060162u
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Semiquinone Radicals in the in Vitro Cytotoxicity of Cigarette Mainstream Smoke

Abstract: Free radicals in cigarette smoke have attracted a great deal of attention because they are hypothesized to be responsible in part for several of the pathologies related to smoking. Hydroquinone, catechol, and their methyl-substituted derivatives are abundant in the particulate phase of cigarette smoke, and they are known precursors of semiquinone radicals. In this study, the in vitro cytotoxicity of these dihydroxybenzenes was determined using the neutral red uptake (NRU) assay, and their radical-forming capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 38 publications
2
18
0
1
Order By: Relevance
“…[16][17][18]24,26,27] The tar contains diverse persistent radicals that can be observed directly by ESR. [16,17,19,21,25] However, the effects of the smoke tar on the LPO development remain unclear. [16,17,26,27] In the present work, addition of tar extracts to liposomes provoked a slight decrease in the DB level as compared with the control samples during the first 20 min after LPO initiation (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18]24,26,27] The tar contains diverse persistent radicals that can be observed directly by ESR. [16,17,19,21,25] However, the effects of the smoke tar on the LPO development remain unclear. [16,17,26,27] In the present work, addition of tar extracts to liposomes provoked a slight decrease in the DB level as compared with the control samples during the first 20 min after LPO initiation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[6,[15][16][17][18][19][20][21][22][23] Cigarette smoke is a complex chemical conglomerate that contains high concentrations of two distinctly different fractions of free radicals, one in its gas phase (GP) and another one in the particulate matter (tar). [16,17,[24][25][26][27] The GP of the smoke predominantly contains reactive carbon-and oxygencentred radicals, as well as a rather sizable amount of nitric oxide. [16,19] Tar contains, most prominently, polycyclic hydrocarbons, polyphenols, and quinones.…”
Section: Introductionmentioning
confidence: 99%
“…The most abundant phenolic compounds identified in cigarette smoke are phenol, dihydroxybenzenes, and their respective methyl-substituted derivatives. Hydroquinone, catechol, and their methyl derivatives have been shown to be toxic [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the semiquinone of CS is cytotoxic (Chouchane et al 2006;Pryor et al 1998). Here we show that a charcoal fi lter, which effectively reduces the p-BSQ of mainstream smoke, also causes a marked reduction in the cytotoxicity of CS.…”
Section: Discussionmentioning
confidence: 99%
“…Once identifi ed, removal of that chemical entity could effectively reduce smokers' risk. Earlier, it was indicated that long-lived semiquinone radical(s) present in an aqueous extract of CS (AECS) is cytotoxic and causes protein and DNA damage (Pryor et al 1983(Pryor et al , 1986(Pryor et al , 1998Panda et al 1999Panda et al , 2000Panda et al , 2001Chouchane et al 2006;Banerjee et al 2008). Protein damage and DNA fragmentation are hallmarks of emphysema (Tuder et al 2003).…”
Section: Introductionmentioning
confidence: 99%